D.J. Opperman : 'Spermutasie' - die palimpses : Elizabeth Maria Magdalena Klopper. - Klopper, Elizabeth Maria Magdalena (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Phil) -- Universiteit van Stellenbosch, 1989.